Effectiveness and efficiency of state aid for new broadband networks: Evidence from OECD member states - Wolfgang Briglauer; Michał Grajek (European School of Management and Technology (ESMT), 2021)
The deployment of new broadband networks (NBNs) based on fiber-optic transmission technologies promises high gains in terms of productivity and economic growth, and has attracted subsidies worth billions from governments around the world in the form of various state aid programs. Yet, the effectiveness and the efficiency of such programs remains largely unstudied. We employ panel data from 32 OECD countries during 2002-2019 to provide robust empirical evidence of both. We find that state aid significantly increases NBNs by facilitating the deployment of new connections to 22% of households in the short term and 39.2% in the long term. By comparing the actual amounts of state aid support to the estimated impact on GDP growth, we also find it to be highly cost efficient, as the programs break even after three years on average.
urn:nbn:de:101:1-2021082508030470783534
Keywords: C51; C54; H25; L52; O38; 650; Fiber optic technology; state aid; ex-post evaluation; efficiency; OECD countries